2020
DOI: 10.3390/educsci10030075
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory School Attendance: The New American Crime

Abstract: A mom walks up to the District Attorney’s desk in the Justice of the Peace Court with a total of six tickets as a result of her low-income children’s truancy, three in her name and one for each of her three children. She faces the possibility of having to pay anywhere from $510 to $2010 in court costs and fines. Luckily for this mother, her children’s cases can be dismissed if she and the children comply with the Judge’s probation terms. In this Court, the court costs are actually at the lowest end of the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…In 2005, the national graduation rate was 70%, with 50% for Native Americans, 55% for Blacks, 58% for Latinxs, 78% for Whites, and 85% for Asians and 68% males and 78% females. Urban areas had a graduation rate of 61% compared to a 75% graduation rate in suburbs [12,16]. In 2009, it was reported that the dropout rate for bilingual students who were denied bilingual classes nearly doubled [17].…”
Section: The History Of Dropouts In the United Statesmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2005, the national graduation rate was 70%, with 50% for Native Americans, 55% for Blacks, 58% for Latinxs, 78% for Whites, and 85% for Asians and 68% males and 78% females. Urban areas had a graduation rate of 61% compared to a 75% graduation rate in suburbs [12,16]. In 2009, it was reported that the dropout rate for bilingual students who were denied bilingual classes nearly doubled [17].…”
Section: The History Of Dropouts In the United Statesmentioning
confidence: 99%
“…All states in the United States have laws governing compulsory education covering school attendance/truancy issues [12]. Most states have framed attendance/truancy policies to hold parents responsible for the actions of their children [minors].…”
Section: Truancy and Get-tough Policiesmentioning
confidence: 99%
See 3 more Smart Citations